(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The word euthanasia Triggers a spate of Controversy worldwide as there are different forms of practicing euthanasia. When a person ends his life by his own act it is called “suicide” but to end life of a person by others though on the request of the deceased, is called “euthanasia” or “mercy killing”. This paper intends to discuss what euthanasia is and its possible application in three different occasions of a living person since very birth. In ancient world how the practice of self-destruction was a customary, what was the viewpoint towards the eradication of life of different religions like Hindu, Muslim, Christian, Jains, Buddha and Sikh. Though the purpose of suicide and euthanasia is self-destruction but there is clear difference between the two. Euthanasia may be classified in five categories and also there are various ways for its implementation. These apart the opinion of sociologists regarding euthanasia, its legal position in Indian Penal Code and other laws in vogue, so also the position of different countries of the world are all taken for consultation. Although the Supreme Court has already given its decision on this point but still some hesitation arise in our point which we need to examine carefully. Finally, arguments are put forward for and against legalizing euthanasia and this article has been ended with a definite remark in favour of legalizing passive euthanasia in India.